2017
DOI: 10.1016/j.ejogrb.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia before and after childbirth: The risk of developing postpartum pain—A longitudinal population-based study

Abstract: Objective: To examine if insomnia before and after childbirth predicts the development of postpartum bodily pain. Methods: This study is part of a longitudinal cohort study, the Akershus Birth Cohort Study, which targeted all women giving birth at Akershus University Hospital in Norway. The current sample is comprised of 1480 women who participated at all three time points, yielding a participation rate of 32% of the 4662 women who originally consented to participate. The Bergen Insomnia Scale (BIS) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…We anticipated that meloxicam treatment would increase activity postcalving regardless of calving difficulty; however, our results oppose our original hypothesis. In human studies, women who had chronic insomnia after childbirth reported higher levels of bodily pain (Sivertsen et al, 2017), and NSAID therapy administered within 24 h of childbirth helped alleviate this pain (Hedayati et al, 2003). It is possible that in the present study administration of meloxicam to dystocic animals reduced activity by alleviating inflammation, allowing the cow to rest more easily, similar to Barrier et al (2014), where meloxicam administration increased lying time after caesarean sections in beef cattle.…”
Section: Effect Of Treatment On Behavioral Responsesmentioning
confidence: 65%
“…We anticipated that meloxicam treatment would increase activity postcalving regardless of calving difficulty; however, our results oppose our original hypothesis. In human studies, women who had chronic insomnia after childbirth reported higher levels of bodily pain (Sivertsen et al, 2017), and NSAID therapy administered within 24 h of childbirth helped alleviate this pain (Hedayati et al, 2003). It is possible that in the present study administration of meloxicam to dystocic animals reduced activity by alleviating inflammation, allowing the cow to rest more easily, similar to Barrier et al (2014), where meloxicam administration increased lying time after caesarean sections in beef cattle.…”
Section: Effect Of Treatment On Behavioral Responsesmentioning
confidence: 65%
“…The physiological factors include genetics, injury and health status. The psychosocial factors include early life factors, 24 female in gender, 20 25 poor sleep, 26–30 distressed mood (depression, anxiety), 31 psychosocial environment (social suffering setting 32 ), perceived stress, 33 religion and self-efficacy (SE). 34 35 The analysis of risk factors of pain among the rural residents in China is required for target people who are at a greater risk and planning and facilitating treatment across rural areas in China.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the odds ratios (ORs) and 95% confidence intervals (95% CIs) to quantify this association. We adjusted for the following confounding variables: age, BMI, parity, and history of LBPP before pregnancy [15,16]. We used the statistical software EZR (version 3.4.1) [17] with the statistical significance set at an alpha level of 0.05.…”
Section: Discussionmentioning
confidence: 99%